Colonic Diverticulitis in the Elderly - Chien-Kuo Liu; Hsi-Hsien Hsu; She-Meng Cheng (International Journal of Gerontology, 2009)
Diverticular disease of the colon is a disease that mainly affects the elderly and presents in 50–70% of those aged 80 years or older. The most common complication is colonic diverticulitis. Eighty percent of patients who present with colonic diverticulitis are aged 50 years and older. Diagnosis and treatment of colonic diverticulitis in the elderly is more difficult and complicated owing to more comorbid conditions. Computed tomography is recommended for diagnosis when colonic diverticulitis is suspected. Most patients admitted with acute colonic diverticulitis respond to conservative treatment, but 15–30% of patients require surgery. Because surgery for acute colonic diverticulitis carries significant rates of morbidity and mortality, conservative treatment is recommended in the elderly. Conservative treatment of colonic diverticulitis with antibiotics, bowel rest, possibly including parenteral alimentation, is usually applied for 1–2 weeks. In the absence of a response to conservative treatment, frequent recurrence or complications (abscesses, fistulas, bowel obstructions, and free perforations), surgery is indicated.